Relative performance evaluation in executive pecuniary compensation: empirical evidences in Brazil - Anjos, Luiz Carlos Marques dos; Neto, Adhemar Ranciaro; Paulo, Edilson; Monte, Paulo Aguiar do (Revista de Administração da UFSM, 2019)
The objective of this study was to analyze the implicit use of relative performance evaluation in BM&FBovespa listed companies as a way to measure the remuneration of its executives. To define the sample, we sought to identify companies that disclosed information about the compensation of their executives between 2009 and 2012, totaling the sample size in 67 companies, totaling 112 observations. They were then categorized in order to capture risk sharing as predicted by the theory of relative performance evaluation. The results of this research indicate a strong asymmetry in the distribution of the compensation, mainly due to the long-term compensation, which caused the occurrence of outliers. As a result of this situation, and following studies already developed, it was decided to test the model through quantile regression. Even with the use of the median regression it was not possible to identify statistically significant evidences of the occurrence of relative performance evaluation, therefore, there is no evidence that the variation of the result of the sector reduces the impacts that the results obtained by the organizations exercise on the executive remuneration.